Live vaccines for Theileria parva: deployment in eastern, Central and Southern Africa. Proceedings of an FAO/OAU-IBAR/ILRI workshop - Morzaria, S.P.; Williamson, S. (International Livestock Research Institute, 1999)
The aim of this workshop was to consider methods of immunisation against East Coast Fever (ECF) and other forms of T. parva infection using the infection and treatment method or infection without treatment, and to identify needs for further research to improve vaccine quality and suitability; to consider present and future demands for T. parva vaccine and how these can be met; to review recent progress in developing alternative vaccines for the control of theileriosis caused by T. parva, to consider related research needs, and to identify training and information needs. The workshop participants discussed the deployment of live ECF vaccines and focused on the problems associated with their delivery and the solutions to these problems. These proceedings provide a record of all the country presentations, invited papers, group discussions and recommendations of the workshop. Topics of discussion include production of Theileria parva stabilates and preparation of a composite stabilate for immunisation, application of molecular tools in support of development, standards for live vaccines, infection and delivery method, vaccine delivery, socio-economics and impact assessment, alternative vaccines, and training requirements for vaccine delivery.